2013
DOI: 10.1016/j.ajog.2013.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with persistent urinary incontinence

Abstract: Objective Many women with urinary incontinence (UI) have symptoms that continue over many years; however, virtually nothing is known about factors that are associated with persistent UI. Study design We studied 36,843 participants of the Nurses’ Health Study, aged 54–79 years at baseline for the UI study, who provided UI information on biennial questionnaires from 2000 to 2008; follow up in the Nurses’ Health Study is 90%. In total, 18,347 women had “persistent UI,” defined as urine leakage ≥1/month reported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 19 publications
1
20
0
1
Order By: Relevance
“…Indeed, in middle-aged women, regular low intensity activity is associated with lower odds of new and persistent SUI. 69 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in middle-aged women, regular low intensity activity is associated with lower odds of new and persistent SUI. 69 …”
Section: Introductionmentioning
confidence: 99%
“…In this respect, waist circumference has been shown to be an important risk factor for the development of UI [8,16]. Intervention studies have demonstrated a decrease of up to 47% in episodes of urine loss with a reduction in body weight [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect related to UI is that regular physical activity helps to reduce body weight, which is an important risk factor in the genesis of UI 12 and minimizes the decline in muscle strength, including pelvic floor muscles (PFM) in older women 11 . Lee and Hirayama 19 assessed the relationship of physical activity with UI and found that the practice of walking an average of 5 hours a week is a protective factor for UI (OR = 0:43; CI 95% = 0.20-0.96) and Kikuchi et al 16 analyzed the relationship of physical activity in the leisure domain with UI and found that moderate (OR = 0.63; CI 95% = 0.42-0.94) and high levels (OR = 0 43; CI 95% = 0.26-0.68) of physical activity are protective factors for UI.…”
Section: Discussionmentioning
confidence: 99%
“…Study participants were intentionally and voluntarily recruited. Inclusion criteria were: being female, because urinary incontinence presents risk factors and is more prevalent in females [2][3][4] , being 60 years or older, due to the higher prevalence of this disease with increasing age 4,12 and physical inactivity 6,7 ; presence of stress or mixed urinary incontinence; frequency of urinary incontinence of at least once a month; and living in the region of Florianópolis, SC. Those showing only urge urinary incontinence were excluded.…”
Section: Study Type and Samplementioning
confidence: 99%
See 1 more Smart Citation